THE ANALYSIS OF STAKEHOLDER SATISFACTION LEVEL TOWARDS THE INTEGRATED SCIENCE EDUCATION GRADUATES - Amalia, Andin Vita; Dewi, Novi Ratna; Savitri, Erna Noor; Fibriana, Fidia (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
There has been limited information about the integrated science education alumni and the graduate user (stakeholder) satisfaction level. Therefore, a concrete step needs to be taken by the department managers in the form of alumni data collection — this research intended to reveal the stakeholders' responses to the Integrated Science Education graduates of Universitas Negeri Semarang. The methods adopted were descriptive-qualitative and quantitative employing questionnaire instruments available on the tracer study web system. The questionnaires had several indicators including (1) ethics and moral, (2) professionalism, (3) insight, (4) leadership, (5) teamwork, (6) foreign language mastery, (7) communication, (8) IT skills, and (9) self-development. Based on the accomplishment score average of the 9 indicators, the graduates categorized as very good having the final score of 3.72. The knowledge background suitability with the jobs scored 3.60 or categorized as very good. The analysis results revealed that of the 9 indicators, 7 of them categorized as ‘very high' (ethics and moral, insight, leadership, teamwork, communication, IT skills, and self-development) and 2 of them categorized as ‘high' (professionalism and foreign language mastery). The integrated science education alumni's suitability of competencies towards the jobs also categorized as ‘very high.'